Pengaruh Lingkungan Sekolah, Kompetensi Guru Dan Pola Asuh Orang Tua Terhadap Motivasi Belajar Siswa Ma Al Fatich Tambak Osowilangun Surabaya - Abdul Latif; Didit Darmawan; Muhammad Yusron Maulana El-Yunusi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Learning activities and educational quality are at the center of educational stages. The quality of education can be assessed based on the discipline of students in the school or community environment and the competence of teachers and parenting patterns . This research aims to reveal the influence of the school environment , teacher competence and parenting patterns on student learning motivation. Quantitative research methods collect data through surveys with questionnaires and direct observation of students. The research results show that a conducive school environment , high teacher competence and parental parenting make a positive contribution to student learning motivation. Factors such as positive relationships between teachers and students, a supportive classroom atmosphere, adequate learning facilities, and the use of innovative teaching methods form a motivating environment for students. Teacher competence in understanding student needs, providing appropriate challenges, and creating positive relationships also plays an important role in increasing student learning motivation. It is hoped that these results can guide educational policies and teacher professional development to increase student learning motivation in the school environment. Parental parenting styles in guiding students also influence the motivation of each student, such as parents who really pay attention to each student's learning needs, communication style and emotional support as well as parental attention to student morals, all of which have an impact on student learning motivation.